Bimbingan Teknis UMKM dalam Penerapan Strategi Pemasaran Digital Berbasis Syariah di Desa Cilembu Kecamatan Tanjungsari - Dewi, Rachmayani; Ishak, Deding; Kania, Inna Ratu; Juhrodin, Udin (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2024)
This community service activity aims to implement sharia-based digital marketing strategies for the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Cilembu Village, Tanjungsari District, Sumedang Regency. Cilembu Village has significant potential for MSMEs; however, many entrepreneurs have not optimally utilized digital technology to market their products. Through this training, participants are taught about digital marketing concepts that align with sharia principles, including the use of social media, creating engaging content, and e-commerce strategies. The methods used include outreach, interactive discussions, and hands-on practice. The results of the activity indicate an improvement in the understanding and skills of MSME actors in applying sharia-based digital marketing strategies. Additionally, entrepreneurs showed increased confidence in marketing their products online, which is expected to enhance competitiveness and improve the economic welfare of the Cilembu community.